2022
DOI: 10.1111/ijpo.12897
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary time has a stronger impact on metabolic health than moderate to vigorous physical activity in adolescents with obesity: a cross‐sectional analysis of the Beta‐JUDO study

Abstract: Summary Background Relationships between movement‐related behaviours and metabolic health remain underexplored in adolescents with obesity. Objectives To compare profiles of sedentary time (more sedentary, SED+ vs. less sedentary, SED−), moderate to vigorous physical activity (MVPA) time (more active, MVPA+ vs. less active, MVPA−) and combinations of behaviours (SED−/MVPA+, SED−/MVPA−, SED+/MVPA+, SED+/MVPA−) in regard to metabolic health. Methods One hundred and thirty‐four subjects (mean age 13.4 ± 2.2 yrs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 84 publications
(120 reference statements)
0
12
0
Order By: Relevance
“…A sedentary lifestyle is associated with low HDL-C for all ages and genders [ 36 , 37 ]. A meta-analysis with 19 randomized controlled trials showed that exercise could improve the cardiometabolic risk factors, lowering the TC, LDL-C, and TGs in obese adolescents with sedentary behavior [ 37 ].…”
Section: Change In Hdl-c Quantity During One’s Lifetimementioning
confidence: 99%
“…A sedentary lifestyle is associated with low HDL-C for all ages and genders [ 36 , 37 ]. A meta-analysis with 19 randomized controlled trials showed that exercise could improve the cardiometabolic risk factors, lowering the TC, LDL-C, and TGs in obese adolescents with sedentary behavior [ 37 ].…”
Section: Change In Hdl-c Quantity During One’s Lifetimementioning
confidence: 99%
“…In children and adolescents with obesity, high screen time has been positively associated with body mass index, high blood pressure, IR, triglyceride, and low HDL-C, independently of PA duration and intensity [25-27]. SED time has been positively associated not only with fat mass, visceral adipose tissue, IR, low HDL-C, and a high cumulative cardiometabolic risk score, but also with liver fat content and surrogate markers of nonalcoholic fatty liver disease, independently of MVPA time [4, 27-29].…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence supports a stepwise approach that might start with targeting SED behaviors (step 1, i.e., supporting a shift from long periods of SED time to daily routines incorporating bouts of PA, even low-intensity PA) prior to increasing MVPA (step 2), when increasing MVPA is not possible in youths with obesity. IR, low HDL-C, and a high cumulative cardiometabolic risk score, but also with liver fat content and surrogate markers of nonalcoholic fatty liver disease, independently of MVPA time [4,[27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…However, one can be very active while also engaging in high amounts of daily sedentary behaviors (SB) (i.e., any waking behavior in a sitting, reclining, or lying posture) [ 6 ]. While strong evidence in adults showed that PA attenuated without eliminating the cardiometabolic risk associated with high SB [ 7 ], pediatric studies of the last decade demonstrated that decreasing SB improved both physical and psychosocial health in youth [ 8 , 9 , 10 , 11 , 12 , 13 ]. Increasing PA and reducing SB would have independent and synergic effects on major health outcomes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…While strong evidence in adults showed that PA attenuated without eliminating the cardiometabolic risk associated with high SB [ 7 ], pediatric studies of the last decade demonstrated that decreasing SB improved both physical and psychosocial health in youth [ 8 , 9 , 10 , 11 , 12 , 13 ]. Increasing PA and reducing SB would have independent and synergic effects on major health outcomes [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Thus, the World Health Organization (WHO) currently recommends at least 60 min of moderate to vigorous PA (MVPA) per day while minimizing SB, in particular screen time, to be less than 2 h per day for children and adolescents [ 20 ].…”
Section: Introductionmentioning
confidence: 99%